THEORETICAL PRINCIPLES OF TEACHING FOREIGN LANGUAGES AS A SECOND FOREIGN LANGUAGE - FOTIMA BOYSARIYEVA, (TADQIQOTLAR, 2026)
ANNOTATION The article is about the most common theories teaching foreign languages as a second languages on the field of higher education. Discuss about  many  theoretical ways of several scholars who worked on the topic. Given some modern ways how to teach English as a second language on higher education and after graduation of our modern education system as well.